Effect of age of seedlings at staggered transplanting and weed management on the growth and yield of aromatic Boro rice (cv. BRRI dhan50) (Journal of the Bangladesh Agricultural University, 2018)
An experiment was conducted at the Agronomy Field Laboratory, Bangladesh Agricultural University, Mymensingh during December 2015 to May 2016 to study the effect of age of seedlings at staggered transplanting and weed management on the growth and yield of aromatic Boro rice (cv. BRRI dhan50). The experiment comprised four seedling ages at staggered transplanting viz. 30, 45, 60 and 75-day old seedlings with five different weed management treatments viz. unweeded controls, two hand weeding at 20 and 35 DAT (days after transplanting), pre-emergence herbicide  (Pendimethaiin, Panida 33EC) applied at 3 DAT  + one hand weeding at 35 DAT, post-emergence herbicide (Penoxsulam, Granite 240 SC) applied at 12 DAT  + one hand weeding at 35 DAT, pre-emergence herbicide (Panida 33 EC) applied at 3 DAT + post-emergence herbicide (Granite 240 SC) applied at 12 DAT. It was observed that the experiment was laid out in a randomized complete block design with three replications. The highest plant height and total dry matter hill–1 were recorded in 30-day old seedlings with pre-emergence herbicide (Panida 33EC) applied at 3 DAT + post-emergence herbicide (Granite 240 SC) applied at 12 DAT. Younger seedlings (30-days old) produced the highest number of total tillers hill–1 (11.08), effective tillers hill–1 (8.47), grains panicle–1 (80.76) and grain yield (3.94 t ha–1) compared to aged seedlings at staggered transplanting. In case of weed management, pre-emergence herbicide (Panida 33EC) applied at 3 DAT + post-emergence herbicide (Granite 240 SC) applied at 12 DAT produced the highest number of effective tillers hill-1 (8.89), grains panicle–1 (81.66), 1000-grain weight (18.44 g), grain yield (4.47 t ha–1) and straw yield (5.13 t ha–1). Grain yield was reduced by 59.82% in unweeded control compared to pre-emergence herbicide (Panida 33EC) applied at 3 DAT + post-emergence herbicide (Granite 240 SC) applied at 12 DAT. In interaction, 30-day old seedlings combined with pre-emergence herbicide (Panida 33 EC) applied at 3 DAT + post-emergence herbicide (Granite 240 SC) applied at 12 DAT produced the highest effective tillers hill–1 (9.58), grains panicle-1 (89.47), 1000-grain weight (18.93g), grain yield (5.31 t ha–1) and straw yield (5.75 t ha–1). Therefore, 60-day old seedlings at staggered transplanting with pre-emergence herbicide (Panida 33EC) applied at 3DAT + post-emergence herbicide (Granite 240 SC) applied at 12 DAT appears as the promising technique for aromatic Boro rice cultivation.J. Bangladesh Agril. Univ. 16(1): 5-11, April 2018